2018
DOI: 10.3390/medsci6020028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Response to PDE5 Inhibitors and Penile Duplex Doppler Ultrasound in Erectile Dysfunction

Abstract: The relationship between the results of penile duplex Doppler ultrasound (PDDU) and response to vardenafil was investigated in patients diagnosed with erectile dysfunction (ED). Data from 148 patients with ED were analyzed retrospectively. Patients who did not respond to therapy were classified in to Group I (n = 32), those who responded partially were classified into Group II (n = 40), and complete responders were classified into Group III (n = 76). Age, comorbidities, and vascular and penile pathologies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Patients with arteriogenic ED still respond to phosphodiesterase type 5 (PDE5) inhibitors 27 29 . In patients with mild-to-moderate ED, up to 60% had normal erectile function after treatment with sildenafil 50 mg for 1 year 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with arteriogenic ED still respond to phosphodiesterase type 5 (PDE5) inhibitors 27 29 . In patients with mild-to-moderate ED, up to 60% had normal erectile function after treatment with sildenafil 50 mg for 1 year 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the long-term use of PDE5 inhibitors might restore normal erectile tissue by improving endothelial function and penile perfusion. However, one study reported that patients with arteriogenic ED seemed to respond less to PDE5 inhibitors than patients with venous insufficiency or non-arteriogenic ED 29 . The results indicate that an accurate diagnosis of arteriogenic ED is crucial for the treatment strategy.…”
Section: Discussionmentioning
confidence: 99%